Pest categorisation of Coniella granati - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; et al. (EFSA Journal, 2023)
Abstract The EFSA Plant Health Panel performed a pest categorisation of Coniella granati, a clearly defined fungus of the Order Diaporthales and the family Schizoparmaceae, described for the first time in 1876 as Phoma granatii and later named as Pilidiella granati. The pathogen mainly affects Punica granatum (pomegranate) and Rosa spp. (rose), causing fruit rot, shoot blight and cankers on crown and branches. The pathogen is present in North America, South America, as well as in Asia, Africa, Oceania and Eastern Europe and has also been reported in the EU (Greece, Hungary, Italy and Spain), where it is widespread in the major pomegranate growing areas. Coniella granati is not included in Commission Implementing Regulation (EU) 2019/2072 and there are no interceptions in the EU. This pest categorisation focused on those hosts for which the pathogen was detected and formally identified in natural conditions. Plants for planting, fresh fruits and as well as soil and other plant growing media are the main pathways for the further entry of the pathogen into the EU. Host availability and climate suitability factors occurring in parts of the EU are favourable for the further establishment of the pathogen. In the area of its present distribution, including Italy and Spain, the pathogen has a direct impact in pomegranate orchards as well as during post‐harvest storage. Phytosanitary measures are available to prevent the further introduction and spread of the pathogen into the EU. Coniella granati does not satisfy the criteria that are within the remit of EFSA to assess for this species to be regarded as potential Union quarantine pest as it is present in several EU MSs.